ANALISIS MANAJEMEN RESIKO TERHADAP MUTU BETON HASIL PRODUKSI READYMIX CONCRETE - ZAITIN NILAWATI; I GEDE PUTU WARKA; ISYA ASHARI (Universitas Mahasaraswati Mataram, 2019)
In business activities faced by a company will not be apart of a risk. Risks that affect quality, for example concrete quality, are one of the influential risks for ready mixed concrete companies. This research was conducted by survey method to employees in concrete laboratories to determine the frequency and effect of risk on the quality of concrete produced in ready mixed concrete which was then analyzed by the Normality Test, Non-parametric Analysis, and AHP (Analytical Hierarchy Process). Concrete quality analysis was also carried out to determine the level of difference in concrete compressive strength in the plan with the compressive strength produced. The results showed that there were 8 out of 31 dominant risk factors produced in each work that affected the quality of the concrete produced, among others: dominant risk factors in concrete material testing work (ie the presence of clay in the aggregate of 14.3% and poor aggregate gradation of 9.8%), dominant risk factor for fresh concrete testing work (i.e. an increase in cement water factor of 7.5% and the occurrence of concrete mixture segregation of 6.5%), dominant risk factor in hard concrete testing work (i.e. there is a small cavity in concrete of 12.5% and cracked concrete is produced due to an initial shrinkage of 7.9%), as well as dominant risk factors for structural work and equipment (i.e. lack of maintenance / maintenance of concrete / curring of 27.0 % and location of unclean cast of 14.5%).